2018
DOI: 10.1080/02640414.2018.1459152
|View full text |Cite
|
Sign up to set email alerts
|

New insight for activity intensity relativity, metabolic expenditure during object projection skill performance

Abstract: This study examined the metabolic cost (METs) of performing object projection skills at three practice trial intervals (6, 12, and 30 seconds). Forty adults (female n = 20) aged 18-30 (M = 23.7 ± 2.9 years) completed three, nine-minute sessions of skill trials performed at 6, 12, and 30 second intervals. Participants performed kicking, throwing and striking trials in a blocked schedule with maximal effort. Average METs during each session were measured using a COSMED K4b2. A three (interval condition) X two (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…However, the results from the present study would agree with assertions made by Duncan et al [14] that the practice of instep passing a football was considered moderate in intensity. The present results would also align with assertions made by Sacko et al [24], based on adult data, that blocked practice of object control skills, including throwing, kicking and striking, resulted in metabolic expenditure that was moderate to vigorous in nature. In the Sacko et al [14] study, children performed each FMS every 6-30 s with maximal force, whereas in the current study passing was performed 10 passes/min or 20 passes/min.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the results from the present study would agree with assertions made by Duncan et al [14] that the practice of instep passing a football was considered moderate in intensity. The present results would also align with assertions made by Sacko et al [24], based on adult data, that blocked practice of object control skills, including throwing, kicking and striking, resulted in metabolic expenditure that was moderate to vigorous in nature. In the Sacko et al [14] study, children performed each FMS every 6-30 s with maximal force, whereas in the current study passing was performed 10 passes/min or 20 passes/min.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research has acknowledged the need to consider the ability of accelerometers to classify activity involving FMS. Recent work by Duncan et al [14] examined how accelerometers classified throwing and catching and instep passing a football, while other work by Sacko et al [24] identified that accelerometery was likely to classify object control skills as comprising light PA, when in fact they were moderate in nature. Sacko et al [15] also identified that tempo of object control skill practice influenced the energy expended in FMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of motor competence and physical fitness is not only linked directly via neuromuscular function, but also indirectly via participation in physical activity, as noted by and various components of physical fitness 4 . The moderate relationship between motor competence and musculoskeletal fitness can be explained by degree of physical effort needed to perform locomotor and object control skills 60 . Performing a motor skill requires high levels of intra-and intermuscular control and coordination in order to accelerate and stop multi-joint micro movements with respect to the requested task (i.e., goal-directed movement), regardless…”
Section: Discussionmentioning
confidence: 99%
“…In particular, fundamental movement skills such as throwing and catching are conceptualized as important and a regular feature of children’s PA (Holfelder and Schott, 2014). Recent research has suggested it is important to specifically understand how the repeated performance of various types of object control skills contributes to activity intensity as there are no published MET values associated with object control skills in children (Sacko et al, 2018). This type of intermittent movement is a noted limitation in accelerometry-based assessment of PA (Trost et al, 2005), and while accelerometer-based assessment of object control skills has been examined in older adults (Hooker et al, 2011), there appears to be no studies that have examined this issue in children.…”
Section: Introductionmentioning
confidence: 99%